Prevalence and predictors of suicidality among medical students in a public university - Tan, Siew Tin; Mohd Sidik, Sherina; Gyanchand Rampal, Lekhraj Rampal; Ibrahim, Normala (Malaysian Medical Association, 2015)
Background: Undergraduate medical students have been the most distressed group among the student population. Depression and anxiety have been found to be more prevalent in this group of students compared to others. Objective: This study was conducted to determine the prevalence and predictors of suicidality among undergraduate medical students in a public university. Methods: This was an analytical cross-sectional study, conducted in a public university in Selangor, Malaysia. Data were collected using self-administered questionnaires from January to February 2013, and analysed using the Statistical Package for Social Sciences Software (version 21). Results: Out of 625 undergraduate medical students, 537 (85.9%) participated in the study. The prevalence of the suicidality among undergraduate medical students was 7.0%. The significant predictors of suicidality based on multiple logistic regression were the respondent’s lifetime suicide attempts (Adjusted Odds Ratio, AOR 10.4, 95% CI 2.7 to 40.9); depression (AOR 5.9, 95% CI 1.5 to 23.0); breaking off a steady love relationship (AOR 5.4, 95% CI 1.3 to 22.4); hopelessness (AOR 4.9, 95% CI 1.1 to 21.6); and something valued being lost or stolen (AOR 4.4, 95% CI 1.2 to 15.9). Conclusion: These findings indicate that mental health care services should be strengthened at university level. The results show a need for an intervention programme to reduce suicidality among the undergraduate medical students.